Bacterial Adaptation in Structured Environments: Lessons from Darwin's Finches. Issue 1 (January 2021) - Harrison, Joe J.; Parsek, Matthew R.; Tseng, Boo Shan
Abstract : Intricate gene regulatory networks control the transition between the planktonic and biofilm lifestyles in bacteria. New evidence from Mhatre et al . uncovers how various adaptive mutations that arose in a key gene at the nexus of signaling networks in Burkholderia cenocepacia led to the emergence of lineages with different ecological roles, enabling stable coexistence of multiple genotypes and increasing productivity of the community.